Sistem Informasi Kegiatan Posyandu Berbasis Web pada Posyandu Sakura Bekasi - fahrina khairunisa; Iwan Mulyana (LPPM STMIK AL MUSLIM, 2022)
Posyandu is an integrated service post that serves the community to check the condition of toddlers, pregnant women and the elderly. Posyandu Sakura is the name of the posyandu in the Koperindag Housing. Currently, the Sakura posyandu still uses a manual system, the manual system in question is that posyandu cadres are still recording data for toddlers, elderly data and other posyandu activities in a book. This method is considered inefficient, so the authors conducted research to help the cadres' tasks to be more practical and efficient. To overcome these problems, the authors intend to develop a web-based Posyandu information system. Posyandu information system that will be made in this research is to use PHP with Visual Studio Code and MySQL database. Data collection was carried out by the author for this study by means of observation and interviews. Keywords: Posyandu, Information System, Web.